The Application of REV-LBM Double Mesh Local Refinement Algorithm in Porous Media Flow Simulation. (31st March 2022) - Niu, Zhongkun; Yang, Zhengming; Luo, Yutian; Zhang, Yapu; Xia, Debin; Zheng, Taiyi; Zhao, Xinli
Abstract : REV-scale LBM (representative elementary volume scale lattice Boltzmann method) provides a possible way for the unified microscopic simulation of transscale seepage combined with pore-scale LBM. However, shown by numerical results, when simulated fluid flows in tight porous media with discrete microfractures or dispersed dissolution pore, the nonphysical oscillation phenomenon will occur in the region of relatively greater velocity gradient, due to the insufficient computational node caused by computational capability constraints. And for that reason, the increase in simulation scale under certain computational capability will be restricted. In order to solve this problem, this paper extends the application of the original LBM local refinement algorithm into REV-LBM and corrects the original REV-LBM velocity processing method, such that REV-scale LBM has a more reasonable local refinement algorithm. Through conventional computation example, this paper proves that the local refinement algorithm can maintain well computational accuracy while at least double the time efficiency and could save more than 30% of CPU time in the practical application. This algorithm has a great potential of application in simulating flows in larger size porous media with complex micro-nano structures and can provide a new idea to transscale simulation in porous media.